CURRÍCULO E EDUCAÇÃO FÍSICA ESCOLAR: ANÁLISE DO ESTADO DA ARTE EM PERIÓDICOS NACIONAIS - Boscatto, Juliano Daniel; Darido, Suraya Cristina (Universidade Estadual de Maringá, 2017)
ABSTRACT The production of knowledge in the field of Physical Education, perpasses by the analysis of thematic areas of the pedagogical subarea and the inherent aspects of the school curriculum. The objective of this study was to analyze academic-scientific production in national journals with the term Curriculum and Physical School Education in the period between 2005 and 2015. The results of research published in the periodicals demonstrate aspects inherent to the organization / systematization of curricular knowledge Of EF, in order to overcome the sportive and procedural nature of teaching practices. There is a need for research to address this problem, in a collaborative dialogue with teachers who are protagonists of everyday educational actions.

RESUMO A produção do conhecimento no campo da Educação Física, perpassa pela análise de temáticas da subárea pedagógica e aos aspectos inerentes ao currículo escolar. Objetivou-se analisar a produção acadêmico-científica em periódicos nacionais com o termo “Currículo e Educação Física Escolar”, no período entre os anos de 2005 a 2015. Os resultados das pesquisas publicadas nos periódicos demonstram aspectos inerentes a organização/sistematização dos saberes curriculares da EF, com vistas a superar o caráter esportivista e procedimental das práticas de ensino. Visualiza-se a necessidade de as pesquisas abordarem essa problemática, em diálogo colaborativo com os professores protagonistas das ações educativas cotidianas.
CURRICULUM AND SCHOOL PHYSICAL EDUCATION: ANALYSIS OF THE STATE OF THE ART IN NATIONAL JOURNAL
Keywords: Physical Education; Curriculum; Basic Education; Educação Física; Currículo; Educação Básica